SN 2009ip at late times – an interacting transient at +2 years. Issue 4 (14th September 2015) - Fraser, Morgan; Kotak, Rubina; Pastorello, Andrea; Jerkstrand, Anders; Smartt, Stephen J.; Chen, Ting-Wan; Childress, Michael; Gilmore, Gerard; Inserra, Cosimo; Kankare, Erkki; Margheim, Steve; Mattila, Seppo; et al.
Abstract: We present photometric and spectroscopic observations of the interacting transient SN 2009ip taken during the 2013 and 2014 observing seasons. We characterize the photometric evolution as a steady and smooth decline in all bands, with a decline rate that is slower than expected for a solely 56 Co-powered supernova at late phases. No further outbursts or eruptions were seen over a two year period from 2012 December until 2014 December. SN 2009ip remains brighter than its historic minimum from pre-discovery images. Spectroscopically, SN 2009ip continues to be dominated by strong, narrow (≲2000 km s − 1 ) emission lines of H, He, Ca, and Fe. While we make tenuous detections of [Fe ii ] λ7155 and [O i ] λλ6300, 6364 lines at the end of 2013 June and the start of 2013 October, respectively, we see no strong broad nebular emission lines that could point to a core-collapse origin. In general, the lines appear relatively symmetric, with the exception of our final spectrum in 2014 May, when we observe the appearance of a redshifted shoulder of emission at +550 km s − 1 . The lines are not blueshifted, and we see no significant near- or mid-infrared excess. From the spectroscopic and photometric evolution of SN 2009ip until 820 d after the start of the 2012a event, we still see no conclusive evidence for core-collapse, although whether any such signs could be masked by ongoing interaction is unclear.